Pengoptimalan Iklan dan Pengembangan Lounge terhadap Peningkatan Pendapatan Non Aeronautical Bandar Udara Fatmawati Soekarno Bengkulu: Penelitian - Miftahul Wahid Nugroho; Ubaedillah; Rini Sadiatmi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Non-aeronautical revenue is a crucial source of income for airports to support operations and increase profitability, particularly at Fatmawati Soekarno Airport in Bengkulu. This study aims to analyze the influence of advertising business optimization and lounge facility development on increasing non-aeronautical revenue at the airport. The research employs a qualitative method using a literature review approach, examining relevant literature and previous studies. The findings indicate that effective management of advertising media—both in print and digital formats—as well as the provision of comfortable and high-quality lounge facilities significantly contribute to attracting passengers and business partners, ultimately enhancing non-aeronautical revenue. However, the study also recognizes that many other factors may influence this revenue stream. Therefore, further research is needed to identify other relevant variables.